Real-world clinical experience of Xultophy in the management of patients with type 2 diabetes in a secondary care clinic. Issue 6 (November 2018) - Williams, David M.; Shrikrishnapalasuriyar, Natasha; Syed, Waheeba; Yin, Win L.; Chudleigh, Richard; Bain, Stephen C.; Price, David E.; Stephens, Jeffrey W.
Abstract: Aims: Xultophy is the first fixed co-formulation pen containing insulin degludec and the glucagon-like peptide-1 (GLP-1) analogue liraglutide, authorized for type 2 diabetes patients since 2014. The aim was to review the clinical effectiveness of Xultophy across two hospitals in Wales. Methods: Retrospective review of patients commenced on Xultophy between April 2016 and January 2018 was taken. Data related to glycemic control, weight and medication use were collected. Results: Ninety-one patients were initiated on Xultophy, and 60 patients had follow-up for at least 6 months with a mean age of 57.3 years (47% male). Xultophy was well-tolerated, however, abdominal cramps and nausea limited use in three patients. Baseline HbA1c and weight were 84.7 mmol/mol and 101.5 kg. There were significant HbA1c reductions of 9.9 mmol/mol (p < 0.0001) and 13.4 mmol/mol (p < 0.008) at 6 and 12 months, and non-significant changes in weight. Patients with an HbA1c over 84 mmol/mol showed the greatest HbA1c improvement over 6-months. Those prescribed insulin prior to Xultophy had less significant improvements in HbA1c than those previously prescribed GLP-1 analogues. Conclusions: There were significant reductions in HbA1c and statistically insignificant weight gain over 12 months. Switching from GLP-1 analogues to Xultophy was associated with a greater HbA1c reduction compared to switching from insulin.